Breaking barriers: Validation of a Spanish oral health knowledge tool to enhance patient-provider communication - Silvia Spivakovsky; Joyce Figueroa; Ryan Richard Ruff (PLoS ONE, 2026)
Objectives This study aimed to develop and validate the Knowledge Related to Oral Health Literacy Spanish (KROHL- S) instrument to assess oral health knowledge among Spanish-speaking adults in the United States, a population facing significant oral health disparities. Design A cross-sectional study was conducted at NYU College of Dentistry. A convenience sample of 175 self-identified Spanish-speaking adults (70% female, mean age 49. 79 years) completed the orally administered KROHL- S questionnaire. Participants, mainly born outside the US (91. 9%), also completed the Comprehensive Measure of Oral Health Knowledge (CMOHK) and a single-item literacy screening tool in Spanish (SILS). Psychometric properties of the KROHL- S, including internal consistency (Cronbach’s alpha), discriminant validity (correlation with CMOHK), and known-group validity (comparison across education levels), were evaluated. Confirmatory factor analysis was used to test the original factor structure. Results The mean KROHL- S score was 8.34 (SD = 5.82), indicating a low level of oral health knowledge in the sample. Internal consistency for the overall KROHL- S was good (Cronbach’s alpha = 0.75), and interrater agreement was high. A moderate positive correlation was found between KROHL- S and CMOHK scores (r = 0.49, p < .0001). Participants with higher education levels showed significantly greater oral health knowledge on the KROHL- S. Confirmatory factor analysis suggested an average fit to the data (RMSEA = 0.064, CFI = 0.86, TLI = 0.83). Conclusion The KROHL- S could be used to assess oral health knowledge among Spanish-speaking adults and incorporates cultural and linguistic aspects, making it suitable for a wider range of individuals. KROHL-S offers a valuable tool for healthcare providers by not only helping identify individuals’ knowledge gaps to guide customized educational interventions but also helping enhance patient-provider communications.